Lengger Edu-Eco-Tourism sebagai Pengembangan Desa Wisata Berbasis Masyarakat - Niken Widyastuti; Krisna Mutiara Wati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Pagerharjo Village, Samigaluh, Kulon Progo is on the buffer of the Borobudur destination which has a variety of tourism resource diversity. One cultural attraction in Pagerharjo Village is the Lengger Tapeng dance. Lengger has become a local symbol for the Pegerharjo people. The natural, cultural and local wisdom tourism potential of the community, Pagerharjo tourism village has a great opportunity to be visited by many tourists. However, village governance, especially towards the development of a tourist village, has not been implemented professionally, resulting in the potential of the Pagerharjo tourism village not being widely known by tourists. The objectives of this PkM include: (1). Increasing tourism competitiveness, (2) Improving the technical quality of guiding tourists in the tourist village of Pagerharjo (3). Improving the ability of human resources in managing the marketing of tourism products in the Pagerharjo tourism village. The method of implementing this PkM is through outreach, observation, mentoring and evaluation. The results of PkM received a positive response from partners, which have raised awareness, concern for the importance of marketing and excellent service to improve the development of Pagerharjo Tourism Village, both through talk shows and excellent service training